Spatial variability of throughfall and stemflow measurements in Amazonian rainforest - Lloyd, Colin R.; Marques o, A. de O. (Agricultural and Forest Meteorology, 1988)
The spatial variability of throughfall and stemflow in Amazonian tropical rainforest is analysed. Statistical tests are used to assess the minimum sampling size and number of gauges required. Random relocation of throughfall gauges is shown to be better than fixed position gauges and random relocation of gauges on a transect line is better than over an area. During the study period, throughfall and stemflow, calculated as percentages of gross rainfall, were 91(± 2) and 1.8(± 1)%, respectively. No attempt was made in this study to investigate storm size dependency of these figures. © 1988.